A serendipitous isolation of cocrystallized platinum–tin complexes: synthesis, structure and theoretical exploration. (23rd November 2020) - Chauhan, Rohit Singh; Singh, Saurabh Kumar; Tyagi, Adish; Golen, James A.; Rheingold, Arnold L.
Abstract : An adduct of co-crystallized platinum–tin fragments has been synthesized and characterized. NBO and EDA analysis have been performed to explore the nature of bonding in fragments, especially the extent of oxophilic character present in tin atoms. Abstract : The reaction of [PtCl2 (P–P)] (P–P = PPh3, dppp) with [R2 Sn(SeC5 H4 N)2 ] (R = Me, Et) afforded an orange co-crystallized product [Pt(κ 2 -SeC5 H4 N)(P–P)R10 Sn5 (μ-O)3 Cl5 ] (P–P = PPh3, dppp; R = Me, Et). The latter complexes can also be obtained by the treatment of [Pt(SeC5 H4 N)2 (dppp)] with R2 SnCl2 (R = Me, Et). These co-crystallized complexes displayed a completely separated core of the platinum selenolate complex along with an organo-oxotin cage compound in the same lattice. These complexes were characterized by elemental analyses, NMR ( 1 H, 31 P, 77 Se, 119 Sn) spectroscopy and scalar relativistic density functional theory (DFT) calculations. The crystal structures of compounds [Pt(κ 2 -SeC5 H4 N)(dppp)Me10 Sn5 (μ-O)3 (μ-Cl)Cl4 ]HCONMe2 (2a ) and [Pt(Cl)(SeC5 H4 N)(P–P)Et10 Sn5 (μ-O)3 Cl5 ] (2b ) were established by single crystal X-ray diffraction analyses. Natural bond orbital (NBO) and energy decomposition analysis (EDA) were carried out in detail to establish the nature of bonding in both cocrystals. Their molecular structure contains nearly the same platinum fragment; however, the only variation that can be observed with the organo-oxotin cage fragment is that the methyl-substituted oxotin compound 2a is Cl-capped and the ethyl substituted one 2b is an O-capped type cluster.